Locking compression plating for osteoporotic and peri-articular fractures: a short term outcome analysis - Ramachandren, N. S.; Anand, M. R. (International Journal of Research in Orthopaedics, 2020)
Background: Peri-articular and osteoporotic fractures of long bones are becoming more common and are very challenging injuries to treat even for a veteran orthopaedician. In young patients, peri-articular fractures occur due to high-velocity injuries such as road traffic accidents, firearm injuries, and sports injuries while in elderly patients with osteoporosis it occurs usually due to low-velocity injury like fall during walking. The aim of the study is to analyze the short term results in terms of union and functional outcome for osteoporotic and periarticular fractures treated with locking compression plating. Methods: This is a study conducted in the Department of Orthopaedics, Government Tiruvarur medical college. Tiruvarur. This study is a prospective study conducted in the Department of Orthopaedics from June 2017 to May 2018 with a sample size of 21 cases. The fracture is classified using the various classification systems earlier described. Results: Solid union was observed in 18 out of the 21 cases (86%) which are similar to other studies. The range of movements attained at an average follow-up of 15.5 months was 87% of which 17 had excellent results, 2 had a good outcome, 1 had the fair outcome and 1 case had poor functional results. Conclusions: The results of our study have confirmed earlier reports that locking compression plates provide better fixation in osteoporotic fractures. The chances of implant failure are less as the screws are firmly positioned inside the bone.